RANCANGAN PENELITIAN UNTUK PEMBELAJARAN MATEMATIKA SEKOLAH DENGAN MENGGUNAKAN MEDIA KOMPUTER (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2008)
Research on school mathematics learning with computer as tutee has been doing by some of student of mathematics education department of UPI for their paper. There are two big points in this kind of research, i.e. making school mathematics learning software and implementing in school. This article discuss about planning of that kind of research.
Keywords: Software; computer as tutee; implementing